2006
DOI: 10.1007/s00259-006-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG—a marker of tumour hypoxia? A comparison with [18F]fluoromisonidazole and pO2-polarography in metastatic head and neck cancer

Abstract: These results support the hypothesis that tumour hypoxia has an effect on glucose metabolism. However, other factors affecting FDG uptake may be more predominant in chronic hypoxia, and thus FDG PET cannot reliably differentiate hypoxic from normoxic tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 33 publications
1
69
0
1
Order By: Relevance
“…Preclinical in vivo studies revealed that (96,302), making it a relevant tracer for imaging tumor hypoxia (Fig. 8).…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical in vivo studies revealed that (96,302), making it a relevant tracer for imaging tumor hypoxia (Fig. 8).…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiamentioning
confidence: 99%
“…However, 18 F-FDG PET imaging, a measure of glucose metabolism, does not distinguish between hypoxic and normoxic tumors when compared against several hypoxia assessment modalities. According to three separate publications, the uptake of 18 F-FDG (SUV max or SUV mean ) in a combined total of 47 H&NC patients was not correlative against common pO 2 descriptors, including HP 2.5 and HP 5 as measured by oxygen-sensitive polarographic electrodes (95,96,302). While there was a reported trend of increasing F-FDG does not appear to be a specific means for assessing tumor hypoxia, its intrinsic value may reside in an ability to help define specific tumor phenotypes that are overtly aggressive, providing mutually complementary information which can be used in conjunction with PET hypoxia data ( Fig.…”
Section: F-ef5 (Pentafluorinated Etanidazole)mentioning
confidence: 99%
“…In vivo animal model studies have shown that intracellular retention of 18 F-FMISO depends on oxygen concentration, and the rate of 18 F-FMISO binding under hypoxic conditions can be up to 28 times greater than binding under normoxic conditions (13). Many clinical studies have demonstrated an excellent correlation between the 18 F-FMISO uptake and oxygenation status of gliomas, non-small cell lung cancer, head and neck cancer, and cervical cancer (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Dearling et al (45) reported increased 18 F-FDG uptake in the hypoxic regions of human tumour xenografts, when compared with that in normoxic regions and Pugachev et al (46) reported a positive correlation between 18 F-FDG uptake and hypoxia assessed by pimonidazole in nude mice bearing prostate tumours. Conversely, Rajendran et al (47) and Zimny et al (41) showed that hypoxia and glucose uptake are not systematically positively correlated, depending on the histological tumour type, and consecutively on the intrinsic intratumoural microenvironmental conditions affecting diversely glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%